Serum level of macrophage migration inhibitory factor predicts severity and prognosis in patients with ischemic stroke. (March 2019) - Wang, Chao-Wei; Ma, Peng-Ju; Wang, Yang-Yang; Yang, Ming; Su, Lin-Lin; Wang, Shuo; Liu, Yan-Xia; Yuan, Bin; Zhao, Jian-Hua
Highlights: High MIF levels were associated with an increased risk of cardiovascular diseases. The aim was to evaluate the association between serum MIF and outcome in ischemic stroke. MIF levels are independently associated with the clinical severity at admission. MIF appears to have an interesting potential as a new prognostic biomarker. MIF might be useful in identifying stroke patients at risk for poor outcomes. Abstract: Objective: To evaluate whether the macrophage migration inhibitory factor (MIF) level in serum of ischemic stroke patients was associated with their clinical severity and early outcome. Methods: During February 2017–March 2018, consecutive patients admitted to our hospital because of first-ever ischemic stroke were identified. The prognostic value of MIF was set for predicting the outcome of these patients at discharge. The results were compared with existing methods, including National Institutes of Health Stroke Scale (NIHSS) score and validated indicators. Results: 289 patients were enrolled. The serum level of all patients was determined (median: 20.6 ng/ml). At admission, 131 patients (45.3%) were evaluated as minor stroke (NIHSS < 5). When serum level of MIF was increased by each 1 ng/ml, the unadjusted and adjusted risk of moderate-to-high clinical severity was elevated by 5% (OR = 1.05 [95% CI: 1.01–1.09], P = 0.006) and 3% (1.03 [1.00–1.08], P = 0.02), respectively. At discharge, 82 patients (28.4%) had poor functional outcomes. The median serum level of MIF was lower in group with good outcomes than that observed in poor outcomes (19.4[15.8–24.2] vs. 24.0[19.9–29.4] ng/ml; P < 0.001). When serum level of MIF was increased by each 1 ng/ml, the unadjusted and adjusted risk of poor outcomes was elevated by 9% (1.09 [1.05–1.13], P < 0.001) and 6% (1.06 [1.02–1.10], P < 0.01), respectively. Conclusions: High MIF levels are independently related to the moderate to high clinical severity in ischemic stroke patients, as well as the poor outcome at discharge.